Histological evaluation of fresh, boiled and dried beef and camel meat (2007)
The Semimembranosus muscle used for the study was excited from the wholesale beef and camel meat of 2-3 years old male animals. The meat were trimmed of all surface fat, bone and connective tissue and chilled for 24 hours. Sizeable pieces of 7- 9 cm within a weight range of 60-80 gram were cut. Two treatments were applied cum; boiling of meat for 30 minutes at 100 °C till uniform doneness was achieved. Secondly treatment involved smoking of boiled meat for 6 hours at 200 °C - 320 °C. The cooking loss, cold shortening, thermal shortening, shear force, water holding capacity and histological observation were measured. The camel meat gave the highest significant value (P<0.05) in cold shortening, shear force and cooking loss compared to beef. The water holding capacity of beef evaluated gave the highest (P<0.05) 68.12 % than 59.09 % obtained for camel meat. Increase in temperature and duration of cooking, increases shrinkage, coagulation, duration of collagen and protein hardening.